The Structural Relationship Between Principal’s Instructional Leadership, Teacher Commitment and Teacher Self-Efficacy in Program Vokasional Menengah Atas (PVMA) in Malaysia - Ais Md Sulbidin; Halizah Awang (Online Journal for TVET Practitioners, 2024)
The academic achievement of students is heavily influenced by the leadership capabilities of school administrators and the commitment and efficacy of teachers in their roles. However, within the Program Vokasional Menengah Atas (PVMA) context, there has been a concerning rise in students failing to meet minimum qualifications annually. This underscores the urgent need to assess the effectiveness of principals' instructional leadership as well as commitment and self-efficacy of teachers. This study aims to identify the interrelationships between instructional leadership, teacher commitment, and self-efficacy, as well as how instructional leadership and teacher commitment impact teacher self-efficacy. Conducted quantitatively, the research utilized surveys adapted from three questionnaires administered to 318 PVMA teachers, employing descriptive and inferential statistical analyses. Results reveal that principals exhibit strong instructional leadership, while teachers demonstrate high levels of commitment and self-efficacy. Significant correlations were found between instructional leadership and teacher self-efficacy, instructional leadership and teacher commitment, and teacher commitment and self-efficacy. The study highlights the positive influence of instructional leadership and teacher commitment on enhancing teacher self-efficacy, emphasizing the pivotal role of principals in fostering a supportive environment that prevents student underachievement. It provides actionable insights for principals, teachers, and education stakeholders to prioritize instructional leadership, improve teacher commitment, and enhance overall effectiveness in educational outcomes. However, limitations include the exclusive focus on PVMA teachers and reliance solely on questionnaire-based data collection. Future research could expand by incorporating additional variables influencing instructional leadership and diversifying the sample population to enrich understanding and applicability across diverse educational contexts.